Representations of transgender Filipinas in Philippine cinema - Castaneda, Maria Katrina B.
This qualitative study examines the thematic representations of transgender Filipinas in Philippine cinema and their social and cultural implications. For the initial results, the thematic representations concentrate on their persona, particularly their language and voice pitch, their qualities and gender expression. Secondly, the research focuses on their occupational portrayals. They were portrayed either as beauticians or as beauty pageant queens. Trans women were also constructed as caricatures within the comedic genre. This particular representation is countered by the humanization of trans women through drama. Thirdly, the study delves into the salient experiences of trans women narrated in cinema such as gender transitioning, forcing of masculinity, short-term relationships, shaming, abuse and harassment.